Evaluasi Kelayakan Finansial Pembangunan: Studi Kasus Gedung Rawat Inap RSUD dr. Hasri Ainun Habibie Gorontalo - Siti Alfariza Bunga; Arfan Utiarahman; Arfan Usman Sumaga (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The improvement of healthcare service quality in Gorontalo Province requires adequate infrastructure, one of which is the construction of an inpatient building at the RSUD dr. Hasri Ainun Habibie. This study aims to assess the financial feasibility of the construction project to support investment decision-making. The method employed includes financial feasibility analysis using the Net Present Value (NPV), Benefit-Cost Ratio (BCR), Internal Rate Of Return (IRR), and Payback Period (PP) approaches. The data used consisted of primary data, in the form of a Cost Budget Plan (RAB), and secondary data, including hospital financial statements and projected operational revenues. The findings show that the project generates a positive NPV of Rp400,466,187,683, a BCR of 1.40 (greater than one), an IRR of 13,188% (higher than the 10% interest rate), and a payback period of 2.35 years (simple) and 2.36 years (discounted). The values indicate that the project is financially feasible for implementation. This study contributes to the planning and development of healthcare infrastructure, serving as a reference for policymakers in prioritizing public sector investments that aim to improve community services.